Strategi Pemasaran Jasa Pendidikan dalam Menarik Minat Siswa Baru - Pujiono; Fera Rochmawati (ANNAHDLIYAH: Jurnal Manajemen Pendidikan Islam, 2025)
Marketing of educational services needs to be carried out by madrasas as a form of school accountability to provide information regarding the condition of schools to the public. MTs Nahdlatul Ulama Karangploso also uses a marketing strategy that is structured so that the programs created can be implemented properly. The focus of the research includes: 1) the education services marketing strategy in attracting new students' interest in MTs NU 2) the results achieved and the constraints experienced from the education services marketing strategy carried out in attracting new students' interest in MTs NU. This research uses qualitative research with descriptive research type. Data collection was carried out through participatory observation, in-depth interviews, and documentation. Test the validity of the data using source triangulation. Data analysis uses data reduction, data presentation and draws conclusions. From the results of this study, it can be obtained 1) marketing strategy for educational services in attracting new students at MTs NU which includes: a) strategies implemented by MTs NU, b) marketing strategies that are in accordance with the education marketing mix. 2) the results achieved and the constraints experienced from the education services marketing strategy in attracting new students at MTs NU which include: a) the success of the MTs NU education services marketing strategy, b) the lack of human resources in the marketing process, c) the minimum number of followers MTs NU social media accounts.